Rebels without Stories: Postcolonial Perspectives on the Literary Representations of Nineteenth Century’s Jamaican Slave Insurrections - Nicora, Flaminia (Advances in Social Sciences Research Journal, 2025)
The paper explores some aspects of the literary representations of Jamaican rebels in the XIXth century, considering some contemporary samples and some literary re-appropriations of Jamaican history in novels written in the first half of the XXth century. In the first decades of the XIXth century, Jamaican black slaves, who largely outnumbered the European colonizers, were the protagonists of a series of rebellions. Even the more relevant episodes of insurgency, however, and key leaders as the black Baptist deacon Sam Sharpe, never became fictional characters. 1816 and 1831 Christmas Rebellion have not been considered suitable literary subjects by their contemporaries. The representation of Jamaican insurgency in the British world was mainly confined to travelogues and personal narratives, as Matthew “Monk”Lewis’s. While racial issues flow through the Gothic novel, there seems to be a single example of Jamaican novel written in English that describes blacks’ resistance and lives in the plantations: Busha’s Mistress. Its author, Cyrus Frances Perkins, a Creole white, wrote it in 1855, when he had left Jamaica for Canada, but the novel was published in twenty instalments in the Daily Telegraph and Jamaica Guardian only in 1911, and has been published in a book only in 2003. Colonizers never trusted their version to fiction, but this novel “is by no means a standard antislavery tract” (Paton 2005), since its standpoint vacillates between the cruelty of slavery and stereotyped portrayals of “half devil and half child” slaves. In the first decades of the XXth century, a few novels have devoted attention to Jamaican slave rebellions and their protagonist, with special regard to the Morant Bay episode. These historical novels attempt to re-appropriate of a significant point in Jamaican history, making clear once again, the role of the novel as genre in the constitution of national identity. Making sense of the national past is an important step towards emancipation from colonial rule.